Trans-radial Angioplasty of Anomalous Origin of Right Coronary Artery from Left Sinus of Valsalva - A Single-centre Experience (Bangladesh Heart Journal, 2020)
Background: Percutaneous coronary intervention (PCI) to anomalous coronary arteries remain a challenge in current practice, but can be overcome with appropriate techniques and devices. The objective of this study is to explore the challenges and techniques for success in PCI of anomalous origin of right coronary artery from left sinus of Valsalva (RCA-LSV) through the trans-radial route.Methods: This study consisted of 13 patients who underwent PCI for an angiographically significant stenosis in RCA-LSV between November 2017 to March 2020. The procedural details including numbers of catheters used, access, hardware, techniques, duration of procedure, volume of contrast and complications were recorded and statistically analysed.Results: The most frequent site for RCA-LSV is at the level of left main stem (LMS) (53.8%), with 30.8% being just above the LMS level and 5.4% being just below the LMS level. Male to female ratio was 5.5:1. Mean age was 53.7±6.7 (range;42-64) years. 76.9% of our patients were diabetic, 92.3% hypertensive, 84.6% dyslipidaemic, smoker & CKD were 23.1% each. PCI was done successfully in 100% cases. Our default route was transradial for coronary angiography. Angioplasty was performed through trans-radial route in 92.3% and transfemoral in 7.7%, with a single case requiring switch over from radial to femoral route. The average number of guide catheters used was (2±1.0), (range:1-4). We used 4 guide catheters in 2 cases, while the rest of the cases were done by single guide catheter. The guide catheter hooked the coronary ostium selectively and off ostium in 46.2% cases each, while in 7.6% cases it was deeply engaged. Anchoring wire to enhance the guide support was used in 7.7% of cases. The mean duration of the procedure was 33.8 minutes (range: 15-65 minutes), the mean volume of contrast used was 61.5 (range:30-150) ml. We used single stent in 61 % cases and two stents in 39 % cases. Average stent diameter was 2.9 (range;2.5-3.50) mm, length was 28.6 (range;12-43) mm. From among a range of guides used for angioplasty, Judkin’s left (JL) and Judkin’s Right (JR) successfully cannulated the RCALSV in 76.9% & 23.1% respectively. We used Ikari Left (IL) guide catheter in RCA-LSV associated with subclavian tortuosity to enhance guide support. Majority of the lesions stented were of ACC/AHA classification of Type A & B lesions (38.5% each), followed by Type C (23%) lesion.Conclusion: To the best of our knowledge, this is the first report of transradial PCI to RCA-LSV in Bangladesh, describing our experiences and techniques, with locally available hardware. PCI of RCA-LSV through radial route is technically challenging but feasible with reasonable amount of contrast and radiation. Proper localization of ostium and selection of suitable guide catheter like JL or IL is the key to success.Bangladesh Heart Journal 2020; 35(1) : 28-38